Nanoencapsulation of hesperetin using basil seed mucilage nanofibers: Characterization and release modeling. (December 2019) - Kurd, Forouzan; Fathi, Milad; Shekarchizadeh, Hajar
Abstract: Hesperetin (HSP) was incorporated into basil seed mucilage (BSM)/polyvinyl alcohol (PVA) nanofibers using an electrospinning method. Encapsulation efficiency values of 96 ± 12, 93 ± 10, and 89 ± 11% and loading capacity values of 10 ± 1, 14 ± 1, and 18 ± 1% were obtained for 10, 15, and 20% (w/w) HSP loaded nanofibers, respectively. Physicochemical properties of nanofibers were measured using scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction and thermogravimetric analysis. Results showed good incorporation of hesperetin in encapsulant. Nanofibers had diameters of 66–210 nm and HSP loaded nanofibers had diameters of 82–320 nm. No chemical reaction between functional groups of ingredients during electrospinning was observed using FTIR and an increase in thermal resistance of HSP was observed using thermogravimetric analysis. Release behavior was investigated using second order, Higuchi, Korsmeyer-Peppas, Hixson-Crowell and Weibull models and data fitted both Fickian and non-Fickian mechanisms. The results suggested that the BSM/PVA nanofibers could be used as a carrier for encapsulation of bioactive ingredients in the food industry with high encapsulation efficiency and physical stability. Highlights: Hesperetin was loaded in basil seed mucilage nanofibers. Nanocarriers increased the stability of hesperetin with high temperatures. Nanofibers can reduce the release of bioactives with acidic conditions.